A Hubble Constant Determination Through Quasar Time Delays and Type Ia Supernovae - Leonardo R. Colaço (Universe)
This paper presents a new model-independent constraint on the Hubble constant (<semantics>H0</semantics>) by anchoring relative distances from Type Ia supernovae (SNe Ia) observations to absolute distance measurements from time-delay strong Gravitational Lensing (SGL) systems. The approach only uses the validity of the cosmic distance duality relation (CDDR) to derive constraints on <semantics>H0</semantics>. By using Gaussian Process (GP) regression to reconstruct the unanchored luminosity distance from the Pantheon+ compilation to match the time-delay angular diameter distance at the redshift of the lenses, one yields a value of <semantics>H0=75.57±4.415</semantics> km/s/Mpc at a 68% confidence level. The result aligns well with the local estimate from Cepheid variables within the <semantics>1σ</semantics> confidence region, indicating consistency with late-universe probes.